PENGARUH RENCANA PEMBANGUNAN TRANSPORTASI MASSAL TERHADAP EMISI GAS BUANG KARBON MONOKSIDA DI SURABAYA - Mochammad Choirul Rizal (AGREGAT, 2017)
The higher growth of vehicles, causing congestion on some roads and may worsen air quality in the city of Surabaya. Surabaya City Government plans to build Mass Transport System as an of efforts to decrease the high growth in the number of private vehicles. It is expected that with mass transportation, carbon monoxide (CO) emissions from transportation sector can decrease and air quality in Surabaya is improving. To know the change of carbon monoxide emission (CO) emission from motor vehicle source due to tram construction plan in Surabaya, it is necessary to do research on the topic. The location of this research is at Jalan Urip Sumoharjo and Jalan Basuki Rahmat.The research methodologi is calculating the amount of CO emissions of the existing condition, in the plan condition when mass transit transport (tram) is not in operation and the plan condition if the trams in operation. CO emission rate calculation is based on an analysis of vehicle speed for each condition.The results show for Urip Sumoharjo Road, estimated CO emission for planned condition if tram operates higher than before before tram operates. Compared with the existing condition, CO emissions at Urip Sumoharjo increased by 20.71% in pre-tram plan conditions, and increased by 36.25% at the time of the plan if the tram operated. As for the Basuki Rahmat Road segment, an approximate amount of CO emissions for the planned conditions if the tram operates lower than at the time before the tram operates. Compared with the existing condition, CO emission levels on Jalan Basuki Rahmat increased by 32.49% under planned conditions before the tram operated, and decreased by 2.98% at the time of the plan if the tram operated. This is thought to be the case because the percentage of private transporters using a tram of 25.43% is not significant compared to the reduction of road capacity for tram lines